Comparison of the sonar recording method and the aerial photography method for mapping seagrass meadows - Poklar, Mojca (Acta geographica Slovenica, 2020)
This article presents a new perspective on the study of the spatial distribution of seagrass meadows, which—due to their sensitivity to coastal hydrodynamics, sediment transport, changes in nutrient content, and disruptions due to human intervention in their environment—are a good indirect indicator of the properties of seawater. Monitoring their extent and characteristics is essential for determining the properties of seawater, but this requires developing a precise methodology that involves acquiring data on the occurrence of seagrass meadows and mapping them. The base data for the survey presented are sonar recording and aerial photography data, which were utilized to create a seabed classification using geographic information systems (GIS). This provided information on the extent and characteristics of the seagrass meadows. Spatial analysis offers a new look at the coastal belt and reveals some new features.